Synthesis of Soai Type 2‐Arylpyrimidine‐5‐carbaldehydes through Desulfurative Cross‐Coupling with Arylboronic Acids. Issue 33 (8th October 2014) - Maltsev, Oleg V.; Rausch, Rodger; Quan, Zheng‐Jun; Hintermann, Lukas
Abstract: A two‐step synthesis of 2‐arylpyrimidine‐5‐carbaldehydes, which are of relevance as substrates for Soai's asymmetric autocatalysis, was realized by exploiting a hidden threefold symmetry in the target core structure. Condensation of Arnold's C 3 ‐symmetric vinamidinium cation with S ‐methylisothiouronium sulfate provides 2‐methylsulfanyl‐pyrimidine‐5‐carbaldehyde; introduction of aryl groups at C‐2 of the latter was accomplished by a Liebeskind–Srogl palladium‐catalyzed desulfurative (de‐methylsulfanylative) coupling with aryl boronic acids to obtain the target compounds1 (14 examples, 60–95 % yield). Abstract : 2‐Arylpyrimidine‐5‐carbaldehydes, which are of relevance as substrates in Soai's asymmetric autocatalysis, are prepared through Liebeskind–Srogl coupling of aryl boronic acids with 2‐methylthiopyrimidine‐5‐carbaldehyde; the latter is obtained in a hydrolytic condensation of two symmetric amidinium salts.